Phytoplankton blooms and the first report of Tripos furca (Ceratium furca) blooms in Cancabato Bay from August 2023 to January 2024 - Salvatierra, Tisha Angeline G.; Yap-Dejeto, Leni G. (2024)
Cancabato Bay is rich in marine resources that provide livelihood to adjacent coastal communities. It is home to milkfish cages and a rehabilitated mangrove area. Recently, a causeway is being built that cuts across the bay. As primary producers, phytoplankton composition could be affected by these anthropogenic activities. Thus, a monthly water sampling was conducted from August 2023 to January 2024 using a 20-µm mesh size plankton net and a WILDCO Alpha water sampler. A total of 74. phytoplankton genera were recorded, of which 54 genera belonged to the class Bacillariophyceae, 13 genera from Dinophyceae, 3 genera from Cyanophyceae, 2 genera from Chlorophyceae, along with 1 genus each from Dictyochophyceae and Raphidophyceae. The highest average cell density was recorded near the mangrove area ( 4.6 plus/minus 4.4 * 10 ^ 5 cells/L), then the milkfish cage culture zone ( 1.4 plus/minus 0.9 * 10 ^ 5 cells/L). and the lowest density ( 8.5 plus/minus 9.3 * 10 ^ 4 cells/L) in open water. Meanwhile, the highest diversity index was reported in the open water (H' = 2.66 plus/minus 0.76) , followed by the mariculture zone (H' = 2.48 plus/minus 0.74) , and the near-mangrove area (H' = 1.82 plus/minus 0.83) Blooms of Skeletonema ( 9.4 plus/minus 0.55 * 10 ^ 4 cells/L and 1.1 plus/minus 0.12 * 10 deg cells/L) Peridinium quinquecorne ( 6.4 plus/minus 1.3 * 10 ^ 5 cells/L), Trichodesmium ( 5.5 plus/minus 1.1 * 10 ^ 4 - 1.3 plus/minus 0.61 * 10 ^ 5 cells/L) together with a first report on Ceratium furca (Tripos furca) blooms ( 1.2 plus/minus 0.15 * 10 ^ 5 cells/L and 1.9 plus/minus 1.5 * 10 ^ 5 cells/L) in the bay were observed. Pearson's correlation exhibited significant relationships between physico-chemical parameters and dominant phytoplankton. Recurrent blooms might be influenced by increased anthropogenic disturbance from the causeway project that may limit water movement making the bay vulnerable to massive fish-killing events.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.